Subjektivitas Kekuasaan Dalam Pemberitaan Media Online - Launa Afkar; Samdar Rery (BPSDMP Kominfo Jakarta, 2020)
At present, the social media newsroom has been widely used to branding images that are certain political symbols, while deconstructing political images. The news portal Detik.com and Kompas.com include those that are widely used to construct or deconstruct certain political images. In the year of politics, where presidential elections will be held, it is difficult to avoid the subjectivity of power sneaking into the media room. This fact is proven through the study of the reporting of the hashtag (#)2019overthepresident’s on the news portal Detik.com and Kompas.com. This descriptive-interpretive qualitative study with the Pan-Kosicki framing analysis found an element of subjectivity in discourse #2019overthepresident’s on both news portals. Judging from the syntactic, script, thematic, and rhetorical elements of analysis there are aspects of subjectivity in the news Detik.com and Kompas.com. Through the language analysis tool on the four elements of Pan-Kosicki, found a tendency to positive framing on #2019Ganti President's hashtag at Detik.com. On the contrary, Kompas.com tends to give negative framing on #2019overthepresident’s hashtag. There is power subjectivity in news framing in both sample media with different variations, accents, and degrees.Saat ini ruang berita media sosial telah banyak digunakan untuk mem-brading citra yang menjadi simbol politik tertentu, sekaligus mendekonstuksi citra politik. Portal berita Detik.com dan Kompas.com termasuk yang cukup banyak dimanfaatkan untuk mengonstruksi atau mendekonstruksi citra politik tertentu. Di tahun politik, ketika pemilihan presiden akan digelar, sulit dihindari subjektivitas kekuasaan menyelinap masuk ke ruang media. Fakta ini dibuktikan melalui kajian pemberitaan tagar (#)2019GantiPresiden di portal berita Detik.com dan Kompas.com. Penelitian ini merupakan penelitian kualitatif bersifat deskriptif-interpretif dengan analisis framing Pan-Kosicki untuk menemukan adanya unsur subjektivitas pemberitaan media online terkait wacana #2019GantiPresiden di kedua portal berita. Hal tersebut dapat diketahui dari elemen analisis sintaksis, skrip, tematik, dan retoris terdapat aspek subjektivitas dalam pemberitaan Detik.com dan Kompas.com. Melalui analisis bahasa pada keempat elemen analisis Pan-Kosicki, ditemukan kecenderungan framing positif pada tagar #2019GantiPresiden di Detik.com. Sebaliknya, Kompas.com cenderung memberi framing negatif pada tagar #2019GantiPresiden. Terdapat subjektivitas kekuasaan dalam framing berita di kedua media sampel dengan variasi, aksentuasi, dan derajat yang berbeda.